Time and Revolution in Jose Maria Luis Mora's work - Pisconte Quispe, Alan Martín (2017)
This paper analyzes an historical work of the Mexican liberal Jose Maria Luis Mora (1794-1850): Mexico y sus Revoluciones (1836). There Mora understands the Mexico's history from categories like revolution and progress, which are very important in the Mora's project of nation. With our analysis about that book, whose author was one of the greatest Mexico's liberal thinker of first half 19th century, it is possible to obtain some precision about Mora's concept of the revolutionary time in the early Mexican nation.